PERLINDUNGAN JURNALIS YANG BERADA DI DAERAH KONFLIK BERSENJATA BERDASARKAN HUKUM HUMANITER INTERNASIONAL - Bayu Saputra; Zulfikar Jayakusuma; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Journalists in areas of international armed conflict play an important role, namely to convey information to the world about events that occur in conflict directly from the scene.But in carrying out their work, journalists and media workers conducting coverage in areas of international armed conflict often face a variety of dangerous risks.They can be victims in military attacks or other acts of violence.This thesis will discuss the protection given to journalists in international armed conflicts based on International Humanitarian Law and its application.Journalists who are in the area of international armed conflict obtain protection as civilians as stipulated in Article 4 (A) paragraph (4) Geneva Convention III 1949 and Article 79 Additional Protocol I 1977.This research is normative juridical research.Namely the research carried out on the principles of law starting from certain fields of legal governance, by first identifying the rules of law that have been formulated in certain laws.In this study, the data sources used were secondary data with primary, secondary and tertiary legal materials carried out by means of library research.From the results of the study it was found that journalists who were in areas of armed conflict were considered as civilians and enjoyed protection that was generally accepted by civilians, as stated in article 4 (A) paragraph (4) III Geneva Conventions 1949 and Article 79 Additional Protocol I 1977. Protection of safety for journalists who carry out their duties at home and abroad, is the responsibility of the country where the journalist originates and the country where the journalist is located.Keywords: Journalists, International Armed Conflict, State Responsibility